NUTMEG AS INSPIRATION FOR BATIK MOTIF IN JARIK AS MODERN KEBAYA PAIR - Pratiwi, Luluh; Cahyana, Agung (Runtas : Journal Of Arts And Culture, 2024)
Creation of the Final Project entitled "Nutmeg as Inspiration For Batik Motif in Jarik as Modern Kebaya Pair" aims to describe the idea and create modern kebaya clothing by applying the nutmeg plant motif as the basic idea of creating batik motifs which then designed in the form of jarik cloth as a complement to modern kebaya clothing, which emphasizes comfort without forgetting the current fashion trends. The main ideas on this work was based on the process of growing nutmeg plants. The process of creation begins with making alternative designs, selected designs, preparing tools and materials, tracing the motifs to the working materials, writing batik from canting, colet, nemboki, second coloring, fixation, ngelorod, making fashion patterns, cutting, sewing, finishing. The technique used in this process is the tulis batik technique with the dyeing process usin colet tutup celup technique. This creation resulted 4 modern kebaya clothes with the title: Jarembah Amala, Palawa Anindhita, Pukau Renjana, Bernas Nuraga. Each named after different character development of nutmeg